Religious perceptions of crime and implications for punitiveness - Seto, Christopher H (Punishment & society, 2022)
This study tests the role of crime perceptions in mediating the relationship between religiosity and punitive attitudes about criminal justice. Specifically, we estimate the effects of (a) religious affiliation and (b) fundamentalism on punitiveness and assess mediation by dispositional attribution of crime, perceived rising crime rates, perceived immigrant crime, and fear of violent victimization. Data are from the 2014 wave of the Chapman Survey on American Fears, a nationally representative sample of adults in the United States (N = 1,573). We estimated religious effects on punitiveness using ordinary least squares regression and assessed mediation by crime perceptions with the Karlson-Holm-Breen (KHB) method. Punitiveness was positively associated with Mainline Protestant affiliation (vs. non-religious), Catholic affiliation (vs. non-religious), and fundamentalism (fundamentalism also largely accounted for heightened punitiveness among Evangelical Protestants). Perceptions of crime accounted for about 60% of the effects of religious affiliation on punitiveness and nearly 100% of the effect of fundamentalism. Perceptions of crime as caused by evil or moral failure, belief in rising crime rates, and perceptions of immigrant crime were important to explaining religious effects on punitiveness, while fear of violence was relatively unimportant. These findings illuminate the perceptual mechanisms underlying religious effects on criminal justice attitudes.